A carbon dioxide capture membrane and preparation method thereof

By using polyether block polyamide film and polyester nonwoven fabric materials in the carbon dioxide capture film, combined with optional carbon nanotube-graphene composite film, the problem of insufficient separation selectivity and permeability of the carbon dioxide capture film in the prior art in the complex gas environment is solved, and efficient and reliable carbon dioxide separation effect is achieved.

CN118341275BActive Publication Date: 2025-03-25JIUZHANG MEMBRANE (BEIJING) TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410641133.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-03-25
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The existing carbon dioxide capture films have insufficient separation selectivity and permeability in complex gas environments, resulting in poor separation effect.

Method used

A carbon dioxide trapping film structure including a base film, polydimethylsiloxane and a separation layer is adopted. The separation layer uses a polyether block polyamide film with a thickness of 20-80 μm, and a polyester nonwoven fabric with a thickness of 0.1-0.3 mm, and a carbon nanotube-graphene composite film with a thickness of 0.5-5 μm can be used.

Benefits of technology

It significantly improves the separation selectivity and permeability of carbon dioxide from other gases, improves separation efficiency, and provides efficient and reliable solutions, providing an ideal carbon dioxide capture solution for industrial production and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004853322060000101
    Figure BDA0004853322060000101
Patent Text Reader

Abstract

The present application relates to the field of multilayer composite membranes, and specifically discloses a carbon dioxide capture membrane and a preparation method thereof. The carbon dioxide capture membrane includes a base membrane, polydimethylsiloxane and a separation layer, wherein the separation layer includes a polyether block polyamide membrane with a thickness of 20-80 μm, and the base membrane includes a polyester non-woven fabric with a thickness of 0.1-0.3 mm; the preparation method thereof is as follows: the base membrane is soaked in water, most of the water is squeezed out through a pressure roller, and then the water droplets on the surface are removed through a high-speed airflow; a layer of polydimethylsiloxane is uniformly coated on the surface of one side of the polyester non-woven fabric, and the separation layer is bonded to the base membrane through polydimethylsiloxane, and then the separation layer is squeezed by a pressure roller and then dried in an oven, and a carbon dioxide capture membrane is obtained after drying. The carbon dioxide capture membrane of the present application has the advantages of improving the separation selectivity and permeability of the carbon dioxide capture membrane in a complex gas environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of multilayer composite membranes, and more specifically, to a carbon dioxide capture membrane and a preparation method thereof. Background Art

[0002] As the global warming problem becomes increasingly serious, carbon dioxide emission reduction has become a common focus of global concern. In order to cope with climate change and promote green development, the Chinese government has increased its research and implementation of carbon dioxide emission reduction technologies in recent years. Carbon dioxide capture and storage technology (CCUS) is one of the important technologies, and its goal is to achieve emission reduction targets by capturing, transporting, utilizing and storing carbon dioxide.

[0003] Among carbon dioxide capture technologies, membrane separation stands out for its high efficiency, energy saving and environmental protection. The membrane separation method uses the selective permeability of specific membrane materials to carbon dioxide to separate carbon dioxide from other gases. The basic principle of this technology lies in the difference in the solubility or diffusion rate of carbon dioxide on both sides of the separation membrane. The technical characteristics of the membrane separation method are mainly reflected in the following aspects: First, the membrane separation method has a high separation efficiency and can achieve high-concentration carbon dioxide capture at low energy consumption; second, the membrane separation method is simple to operate, occupies a small area, and is easy to integrate and apply in industrial sites.

[0004] Although carbon dioxide capture membranes have advantages such as energy saving and environmental protection, there are still some problems in practical applications. Among them, poor separation effect is one of the main problems. The selectivity and permeability of existing carbon dioxide capture membranes need to be improved, especially when mixed with other gases (such as nitrogen, methane, etc.), which affects its application in industrial production and environmental protection. Summary of the invention

[0005] In order to improve the separation selectivity and permeability of a carbon dioxide capture membrane in a complex gas environment, the present application provides a carbon dioxide capture membrane and a preparation method thereof.

[0006] In the first aspect, the present application provides a carbon dioxide capture membrane using the following technical solution:

[0007] A carbon dioxide capture membrane comprises a base membrane, polydimethylsiloxane and a separation layer, wherein the separation layer comprises a polyether block polyamide membrane with a thickness of 20-80 μm, and the base membrane comprises a polyester non-woven fabric with a thickness of 0.1-0.3 mm.

[0008] By adopting the above technical solution, firstly, the polyether block polyamide has a polyamide structure between a thermoplastic elastomer and a rubber body, which makes the polyether block polyamide membrane highly selective for carbon dioxide molecules, and realizes the effective separation of carbon dioxide and other gases. Since the separation layer adopts a highly selective polyether block polyamide membrane, the capture membrane can efficiently and accurately separate carbon dioxide in a complex gas environment, greatly improving the separation efficiency. Secondly, polydimethylsiloxane enhances the permeability of the membrane due to the flexibility and low surface energy of its molecular chain, allowing gas molecules to pass through the membrane layer more easily. In addition, the low surface energy and hydrophobicity of polydimethylsiloxane help to reduce the adsorption and obstruction of gas molecules on the membrane surface, allowing gas molecules to pass through the membrane pores more smoothly, thereby improving the overall processing efficiency. In addition, the base membrane is made of polyester non-woven fabric material, which has good stability and mechanical strength, can resist certain pressure and deformation, and ensure the stability and reliability of the capture membrane during actual use. In summary, the carbon dioxide capture membrane achieves high-selectivity and high-permeability carbon dioxide separation by optimizing material selection and structural design, providing an efficient and reliable solution for industrial production and environmental protection.

[0009] Optionally, the base film further comprises a bisphenol A type PSF film with a thickness of 100-200 μm.

[0010] By adopting the above technical solution, the bisphenol A type PSF membrane provides additional support for the base membrane with its excellent mechanical strength. During the gas separation process, the membrane will be subjected to a certain amount of pressure and deformation, and the addition of the PSF membrane can effectively enhance the mechanical properties of the base membrane, such as tensile strength and tear resistance, thereby ensuring the stability and reliability of the capture membrane in long-term use. The bisphenol A type PSF membrane has excellent chemical stability and can resist corrosion from a variety of chemical substances. This feature enables the base membrane to maintain stable performance in a complex gas environment and is not easily contaminated or damaged, thereby extending the service life of the capture membrane.

[0011] Optionally, the preparation method of the polyether block polyamide membrane is:

[0012] A1, dispersing nano-silica in ethanol, adding polyethylene glycol, using ultrasonic dispersion to obtain a nano-silica solution, dissolving polyether block polyamide in chloroform to form a uniform solution, the mass ratio of nano-silica to polyether block polyamide is (1-3):10;

[0013] A2, mixing the nano-silica solution with the polyether block polyamide solution, and stirring at a speed of 1200-1500 r / min for 5-10 min;

[0014] A3. The mixed solution is evenly coated on a glass substrate by a doctor blade, and then dried under ventilation at 25-30°C and 40-50% humidity. After drying, a polyether block polyamide film is obtained. The polyether block polyamide film is placed in a nitrogen environment, heated to 100-140°C, kept warm for 2-4 hours, and then cooled to room temperature in a nitrogen environment.

[0015] By adopting the above technical solution, nano-silica is uniformly dispersed in ethanol by ultrasonic dispersion and mixed with polyethylene glycol to form a nano-silica solution. This dispersion method ensures the uniformity and stability of nano-silica particles and avoids the problem of particle agglomeration or precipitation. At the same time, the addition of polyethylene glycol may play a role in adjusting the viscosity and surface tension of the solution, which is helpful for the dissolution and mixing of polyether block polyamide in the subsequent steps.

[0016] Nano-silica is evenly dispersed in the polyether block polyamide matrix to form a stable composite structure, which significantly improves the mechanical strength, thermal stability and chemical corrosion resistance of the polyether block polyamide membrane, thereby improving the service life and reliability of the membrane. The addition of nano-silica optimizes the structure and porosity of the membrane, which helps to improve the separation efficiency and separation selectivity. The molecular sieve effect of nano-silica can help improve the selectivity of the membrane for specific gases and improve the separation efficiency.

[0017] Heating and keeping the polyether block polyamide membrane in a nitrogen environment, and then cooling it to room temperature in a nitrogen environment, helps eliminate residual stress in the membrane and improves crystallinity, thereby further enhancing the performance of the polyether block polyamide membrane. The protection of the nitrogen environment can prevent the membrane from being affected by oxidation during the heating process, ensuring the quality and stability of the membrane.

[0018] Optionally, the separation layer further includes a carbon nanotube-graphene composite membrane with a thickness of 0.5-5 μm.

[0019] Optionally, the preparation method of the carbon nanotube-graphene composite film is as follows:

[0020] B1, dispersing carbon nanotubes and graphene in N,N-dimethylformamide, wherein the mass ratio of carbon nanotubes to graphene is (3-5):7, and then adding phenylenediamine in an amount of 10-30% of the total mass of the carbon nanotubes and graphene, and uniformly dispersing by magnetic stirring to obtain a suspension;

[0021] B2. Spray the suspension on the surface of the polyether block polyamide membrane, introduce nitrogen, heat to 120-140°C and keep warm for 30-60 minutes, then cool to 90-100°C and apply a pressure of 1-5 MPa for 30-60 seconds to form a carbon nanotube-graphene composite membrane.

[0022] By adopting the above technical solution, the π-π interaction and van der Waals force between graphene and carbon nanotubes are utilized to combine carbon nanotubes with graphene to form a three-dimensional structure and prepare an inorganic separation membrane. Graphene can be used as a barrier, and the functional groups on its surface can interact with carbon dioxide gas, thereby providing higher selectivity, while carbon nanotubes provide high permeability as gas transmission channels. This composite membrane has excellent adsorption and transmission properties for carbon dioxide molecules, but has low permeability to other gases (such as nitrogen, methane, etc.). The introduction of carbon nanotube-graphene composite membrane can further improve the permeability of the separation layer and accelerate the diffusion rate of gas molecules in the membrane, thereby improving the separation efficiency of the entire capture membrane.

[0023] When the carbon nanotube-graphene composite membrane is used in combination with the polyether block polyamide membrane, a synergistic effect can be formed, making the entire membrane material more selective for carbon dioxide and less permeable to other gases, thereby greatly improving the gas separation efficiency.

[0024] Optionally, the viscosity of the polydimethylsiloxane is 4000-6000cps.

[0025] By adopting the above technical solution, the viscosity of polydimethylsiloxane provides ideal adhesion within this range, so that it can effectively and tightly bond with the separation layer and base membrane to maintain the overall performance and stability of the carbon dioxide capture membrane. In the range of 4000-6000cps, polydimethylsiloxane can still maintain good gas permeability. This is due to the flexibility of the polydimethylsiloxane molecular chain and its non-polar characteristics, which allows gas molecules to pass through the membrane layer more easily, while ensuring good adhesion and providing an effective transmission channel for gas molecules.

[0026] In a second aspect, the present application provides a method for preparing a carbon dioxide capture membrane, using the following technical solution: A method for preparing a carbon dioxide capture membrane, comprising the following steps:

[0027] S1, soak the base film in water and squeeze out most of the water through a pressure roller, and then pass it through a high-speed airflow to remove water droplets on the surface;

[0028] S2. A layer of polydimethylsiloxane is uniformly coated on one surface of the polyester non-woven fabric. The separation layer is bonded to the base film through the polydimethylsiloxane. The separation layer is squeezed by a roller and then put into an oven for drying. After drying, a carbon dioxide capture membrane is obtained.

[0029] Optionally, the step S1 further includes the following operation: covering the bisphenol A type PSF film on the polyester non-woven fabric, and hot pressing at 110-125° C. and a pressure of 1-3 MPa for 5-15 minutes to obtain a base film.

[0030] By adopting the above technical solution, the base film is immersed in water, extruded by a pressure roller and dehydrated by a high-speed airflow, ensuring the dryness and cleanliness of the surface, providing a good foundation for the subsequent coating process. Then, polydimethylsiloxane is evenly coated on the surface of one side of the polyester non-woven fabric, and it is tightly combined with the base film by pressure roller extrusion to form a stable and reliable capture layer. Finally, the coating is solidified and the residual solvent is removed through a drying process, thereby improving the purity and stability of the capture membrane. The carbon dioxide capture membrane obtained by this preparation method not only has excellent gas separation performance, but also has high mechanical strength and durability, and can maintain a stable capture effect for a long time.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. Since the present application uses polyether block polyamide as the separation layer, it achieves a high degree of selectivity for carbon dioxide molecules, effectively separates carbon dioxide from other gases, and significantly improves the separation efficiency. At the same time, the addition of polydimethylsiloxane enhances the permeability of the membrane, allowing gas molecules to pass through the membrane layer more smoothly, further improving the processing efficiency. In addition, the base membrane is made of polyester non-woven fabric material to ensure the stability and reliability of the capture membrane in actual use. The capture membrane realizes efficient and reliable carbon dioxide separation, provides an ideal solution for industrial production and environmental protection, and achieves excellent results of efficient separation and stable operation.

[0033] 2. In this application, the carbon nanotube-graphene composite membrane, which is a three-dimensional structure formed by combining graphene and carbon nanotubes, is preferably used, which exhibits efficient adsorption and transmission characteristics for carbon dioxide, while significantly inhibiting the penetration of other gases. The introduction of the composite membrane improves the permeability of the separation layer, accelerates the diffusion of gas molecules in the membrane, and thus greatly improves the separation efficiency of the capture membrane.

[0034] 3. The method of the present application realizes the preparation of a highly selective and highly permeable carbon dioxide capture membrane through a simple process, solving the problem of complex process and difficulty in large-scale mass production in the existing composite membrane preparation process. DETAILED DESCRIPTION

[0035] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0036] Preparation Example of Polyether Block Polyamide Membrane

[0037] Preparation Example 1

[0038] The preparation method of the polyether block polyamide membrane is as follows:

[0039] A1, 1kg of nano-silica was dispersed in 1kg of ethanol, 100g of polyethylene glycol was added, and ultrasonic dispersion was performed using an ultrasonic vibrator, the frequency was set to 40KHz, and the treatment was performed for 10min to obtain a nano-silica solution, 10kg of polyether block polyamide was dissolved in 10kg of chloroform, and stirred with a stirrer to form a uniform solution;

[0040] A2, mixing the nano-silica solution with the polyether block polyamide solution, and stirring at a speed of 1400 r / min for 8 min using a high-speed stirrer;

[0041] A3. The mixed solution is evenly coated on a glass substrate by a doctor blade, and dried under ventilation at 28°C and 45% humidity. This process is repeated several times until the film layer reaches 50 μm ± 10 μm after drying. After drying, a polyether block polyamide film is obtained. The polyether block polyamide film is placed in a nitrogen environment, heated to 120°C, kept warm for 3 hours, and then cooled to room temperature in a nitrogen environment.

[0042] Preparation Example 2

[0043] The preparation method of the polyether block polyamide membrane is as follows:

[0044] A1, 2kg of nano-silica was dispersed in 1kg of ethanol, 100g of polyethylene glycol was added, and ultrasonic dispersion was performed using an ultrasonic vibrator, the frequency was set to 40KHz, and the treatment was performed for 10min to obtain a nano-silica solution, 10kg of polyether block polyamide was dissolved in 10kg of chloroform, and stirred with a stirrer to form a uniform solution;

[0045] A2, mixing the nano-silica solution with the polyether block polyamide solution, and stirring at a speed of 1400 r / min for 8 min using a high-speed stirrer;

[0046] A3. The mixed solution is evenly coated on a glass substrate by a doctor blade, and dried under ventilation at 28°C and 45% humidity. This process is repeated several times until the film layer reaches 50 μm ± 10 μm after drying. After drying, a polyether block polyamide film is obtained. The polyether block polyamide film is placed in a nitrogen environment, heated to 120°C, kept warm for 3 hours, and then cooled to room temperature in a nitrogen environment.

[0047] Preparation Example 3

[0048] The preparation method of the polyether block polyamide membrane is as follows:

[0049] A1, 3kg of nano-silica was dispersed in 1kg of ethanol, 100g of polyethylene glycol was added, and ultrasonic dispersion was performed using an ultrasonic vibrator, the frequency was set to 40KHz, and the treatment was performed for 10min to obtain a nano-silica solution, 10kg of polyether block polyamide was dissolved in 10kg of chloroform, and stirred with a stirrer to form a uniform solution;

[0050] A2, mixing the nano-silica solution with the polyether block polyamide solution, and stirring at a speed of 1400 r / min for 8 min using a high-speed stirrer;

[0051] A3. The mixed solution is evenly coated on a glass substrate by a doctor blade, and dried under ventilation at 28°C and 45% humidity. This process is repeated several times until the film layer reaches 50 μm ± 10 μm after drying. After drying, a polyether block polyamide film is obtained. The polyether block polyamide film is placed in a nitrogen environment, heated to 120°C, kept warm for 3 hours, and then cooled to room temperature in a nitrogen environment.

[0052] Preparation Example 3

[0053] The preparation method of the polyether block polyamide membrane is as follows:

[0054] A1. Dissolve 10 kg of polyether block polyamide in 10 kg of chloroform and stir with a stirrer to form a uniform solution;

[0055] A2. The polyether block polyamide solution is evenly coated on a glass substrate by a doctor blade, and dried under ventilation at 28° C. and 45% humidity. The process is repeated several times until the film layer after drying reaches 50 μm±10 μm. After drying, a polyether block polyamide film is obtained. The polyether block polyamide film is placed in a nitrogen environment, heated to 120° C., kept warm for 3 hours, and then cooled to room temperature in a nitrogen environment.

[0056] Example

[0057] Example 1

[0058] A method for preparing a carbon dioxide capture membrane:

[0059] S1. Soak a polyester nonwoven fabric with a thickness of 0.2 mm in water and squeeze out most of the water through a pressing roller, and then pass it through a high-speed airflow to remove water droplets on the surface under the action of the airflow;

[0060] S2. A layer of polydimethylsiloxane with a viscosity of 5000cps is uniformly coated on one surface of the polyester non-woven fabric, and the polyether block polyamide membrane is bonded to the base membrane through the polydimethylsiloxane. After being squeezed by a pressure roller at a pressure of 500Pa, the excess polydimethylsiloxane squeezed out is removed, and the membrane is put into an oven for hot air drying at 80°C to obtain a carbon dioxide capture membrane after drying.

[0061] Wherein, the polyether block polyamide membrane is prepared by Preparation Example 2.

[0062] Example 2

[0063] A method for preparing a carbon dioxide capture membrane:

[0064] S1. Cover a bisphenol A type PSF film with a thickness of 150 μm ± 10 μm on a polyester non-woven fabric with a thickness of 0.2 mm, and hot-press at 120° C. and a pressure of 2 MPa for 10 min to obtain a base film. After soaking the base film in water, most of the water is squeezed out through a pressing roller, and then the base film is passed through a high-speed airflow to remove water droplets on the surface under the action of the airflow;

[0065] S2. A layer of polydimethylsiloxane with a viscosity of 5000cps is evenly coated on one surface of the polyester non-woven fabric in the base film. The polyether block polyamide membrane is bonded to the base film through the polydimethylsiloxane. After being squeezed by a pressure roller at a pressure of 500Pa, the excess polydimethylsiloxane squeezed out is removed, and the membrane is put into an oven for hot air drying at 80°C to obtain a carbon dioxide capture membrane after drying.

[0066] Wherein, the polyether block polyamide membrane is prepared by Preparation Example 2.

[0067] Example 3

[0068] A method for preparing a carbon dioxide capture membrane:

[0069] S1. Cover a bisphenol A type PSF film with a thickness of 150 μm ± 10 μm on a polyester non-woven fabric with a thickness of 0.2 mm, and hot-press at 120° C. and a pressure of 2 MPa for 10 min to obtain a base film. After soaking the base film in water, most of the water is squeezed out through a pressing roller, and then the base film is passed through a high-speed airflow to remove water droplets on the surface under the action of the airflow;

[0070] S2, dispersing 3kg of carbon nanotubes and 7kg of graphene in 10kg of N,N-dimethylformamide, adding 2kg of phenylenediamine, and dispersing them evenly by magnetic stirring to obtain a suspension, spraying the suspension on the surface of the polyether block polyamide membrane by ultrasonic spraying equipment to form a uniform coating, introducing nitrogen, heating to 130°C and keeping the temperature for 45min, then cooling to 95°C and applying a pressure of 3MPa for 40s to form a carbon nanotube-graphene composite membrane with a thickness of 2.5μm±0.5μm, with the composite membrane of the polyether block polyamide membrane and the carbon nanotube-graphene composite membrane serving as a separation layer;

[0071] S3. A layer of polydimethylsiloxane with a viscosity of 5000cps is uniformly coated on one surface of the polyester non-woven fabric in the base film, and the separation layer is bonded to the base film through the polydimethylsiloxane. After being squeezed by a pressure roller at a pressure of 500Pa, the excess polydimethylsiloxane squeezed out is removed, and the film is put into an oven for hot air drying at 80°C to obtain a carbon dioxide capture membrane after drying.

[0072] Wherein, the polyether block polyamide membrane is prepared by Preparation Example 2.

[0073] Example 4

[0074] A method for preparing a carbon dioxide capture membrane: The difference from Example 3 is that the polyether block polyamide membrane is prepared by Preparation Example 1.

[0075] Example 5

[0076] A method for preparing a carbon dioxide capture membrane: The difference from Example 3 is that the polyether block polyamide membrane is prepared by Preparation Example 3.

[0077] Example 6

[0078] A method for preparing a carbon dioxide capture membrane: The difference from Example 3 is that 4 kg of carbon nanotubes and 7 kg of graphene are dispersed in 10 kg of N,N-dimethylformamide, and then 2.2 kg of phenylenediamine is added, and the mixture is evenly dispersed by magnetic stirring to obtain a suspension, and the suspension is sprayed on the surface of a polyether block polyamide membrane using an ultrasonic spraying device to form a uniform coating, nitrogen is introduced, and the mixture is heated to 130°C and kept warm for 45 minutes, and then cooled to 95°C and a pressure of 3 MPa is applied for 40 seconds to form a carbon nanotube-graphene composite membrane with a thickness of 2.5 μm ± 0.5 μm, wherein a composite membrane of the polyether block polyamide membrane and the carbon nanotube-graphene composite membrane serves as a separation layer.

[0079] Example 7

[0080] A method for preparing a carbon dioxide capture membrane: The difference from Example 3 is that 5 kg of carbon nanotubes and 7 kg of graphene are dispersed in 10 kg of N,N-dimethylformamide, and then 2.4 kg of phenylenediamine is added, and the mixture is evenly dispersed by magnetic stirring to obtain a suspension, and the suspension is sprayed on the surface of a polyether block polyamide membrane using an ultrasonic spraying device to form a uniform coating, nitrogen is introduced, and the mixture is heated to 130°C and kept warm for 45 minutes, and then cooled to 95°C and a pressure of 3 MPa is applied for 40 seconds to form a carbon nanotube-graphene composite membrane with a thickness of 2.5 μm ± 0.5 μm, wherein a composite membrane of the polyether block polyamide membrane and the carbon nanotube-graphene composite membrane serves as a separation layer.

[0081] Example 8

[0082] A method for preparing a carbon dioxide capture membrane: The difference from Example 3 is that the viscosity of the polydimethylsiloxane is 3000 cps.

[0083] Example 9

[0084] A method for preparing a carbon dioxide capture membrane: The difference from Example 3 is that the viscosity of the polydimethylsiloxane is 7000 cps.

[0085] Comparative Example

[0086] Comparative Example 1

[0087] A method for preparing a carbon dioxide capture membrane:

[0088] S1. Cover a bisphenol A type PSF film with a thickness of 150 μm ± 10 μm on a polyester non-woven fabric with a thickness of 0.2 mm, and hot-press at 120° C. and a pressure of 2 MPa for 10 min to obtain a base film. After soaking the base film in water, most of the water is squeezed out through a pressing roller, and then the base film is passed through a high-speed airflow to remove water droplets on the surface under the action of the airflow;

[0089] S2, dispersing 3kg of carbon nanotubes and 7kg of graphene in 10kg of N,N-dimethylformamide, adding 2kg of phenylenediamine, and dispersing them evenly by magnetic stirring to obtain a suspension, spraying the suspension on the surface of the polyether block polyamide membrane by ultrasonic spraying equipment to form a uniform coating, introducing nitrogen, heating to 130°C and keeping the temperature for 45min, then cooling to 95°C and applying a pressure of 3MPa for 40s to form a carbon nanotube-graphene composite membrane with a thickness of 2.5μm±0.5μm, with the composite membrane of the polyether block polyamide membrane and the carbon nanotube-graphene composite membrane serving as a separation layer;

[0090] S3. A layer of polydimethylsiloxane with a viscosity of 5000cps is uniformly coated on one surface of the polyester non-woven fabric in the base film, and the separation layer is bonded to the base film through the polydimethylsiloxane. After being squeezed by a pressure roller at a pressure of 500Pa, the excess polydimethylsiloxane squeezed out is removed, and the film is put into an oven for hot air drying at 80°C to obtain a carbon dioxide capture membrane after drying.

[0091] Among them, the polyether block polyamide membrane is prepared by Preparation Example 4.

[0092] Comparative Example 2

[0093] A method for preparing a carbon dioxide capture membrane:

[0094] S1. Cover a bisphenol A type PSF film with a thickness of 150 μm ± 10 μm on a polyester non-woven fabric with a thickness of 0.2 mm, and hot-press at 120° C. and a pressure of 2 MPa for 10 min to obtain a base film. After soaking the base film in water, most of the water is squeezed out through a pressing roller, and then the base film is passed through a high-speed airflow to remove water droplets on the surface under the action of the airflow;

[0095] S2, dispersing 10 kg of carbon nanotubes in 10 kg of N, N-dimethylformamide, adding 2 kg of phenylenediamine, and dispersing them evenly by magnetic stirring to obtain a suspension, spraying the suspension on the surface of the polyether block polyamide membrane by ultrasonic spraying equipment to form a uniform coating, introducing nitrogen, heating to 130 ° C for 45 min, and then cooling to 95 ° C and applying a pressure of 3 MPa for 40 s to form a carbon nanotube membrane with a thickness of 2.5 μm ± 0.5 μm, with the composite membrane of the polyether block polyamide membrane and the carbon nanotube membrane as a separation layer;

[0096] S3. A layer of polydimethylsiloxane with a viscosity of 5000cps is uniformly coated on one surface of the polyester non-woven fabric in the base film, and the separation layer is bonded to the base film through the polydimethylsiloxane. After being squeezed by a pressure roller at a pressure of 500Pa, the excess polydimethylsiloxane squeezed out is removed, and the film is put into an oven for hot air drying at 80°C to obtain a carbon dioxide capture membrane after drying.

[0097] Wherein, the polyether block polyamide membrane is prepared by Preparation Example 2.

[0098] Comparative Example 3

[0099] A method for preparing a carbon dioxide capture membrane:

[0100] S1. Cover a bisphenol A type PSF film with a thickness of 150 μm ± 10 μm on a polyester non-woven fabric with a thickness of 0.2 mm, and hot-press at 120° C. and a pressure of 2 MPa for 10 min to obtain a base film. After soaking the base film in water, most of the water is squeezed out through a pressing roller, and then the base film is passed through a high-speed airflow to remove water droplets on the surface under the action of the airflow;

[0101] S2, dispersing 10kg of graphene in 10kg of N,N-dimethylformamide, adding 2kg of phenylenediamine, and dispersing evenly by magnetic stirring to obtain a suspension, spraying the suspension on the surface of the polyether block polyamide membrane by ultrasonic spraying equipment to form a uniform coating, introducing nitrogen, heating to 130°C for 45min, then cooling to 95°C and applying a pressure of 3MPa for 40s to form a graphene membrane with a thickness of 2.5μm±0.5μm, and a composite membrane composed of the polyether block polyamide membrane and the graphene membrane as a separation layer;

[0102] S3. A layer of polydimethylsiloxane with a viscosity of 5000cps is uniformly coated on one surface of the polyester non-woven fabric in the base film, and the separation layer is bonded to the base film through the polydimethylsiloxane. After being squeezed by a pressure roller at a pressure of 500Pa, the excess polydimethylsiloxane squeezed out is removed, and the film is put into an oven for hot air drying at 80°C to obtain a carbon dioxide capture membrane after drying.

[0103] Wherein, the polyether block polyamide membrane is prepared by Preparation Example 2.

[0104] Performance testing

[0105] Detection Methods

[0106] CO2 / N2 and CO2 / CH4 mixed gases (high-pressure gas cylinders) were respectively prepared, and the carbon dioxide capture membranes prepared in Examples 1-9 and Comparative Examples 1-3 were placed on the test bench. The mixed gas was introduced into one side of the carbon dioxide capture membrane. After the mixed gas passed through the carbon dioxide capture membrane, a flow meter was used to measure the output gas flow rate on the other side of the carbon dioxide capture membrane. The output gas was collected, and the composition of the output gas was measured by a gas chromatograph, and then calculated using the formula:

[0107] R i =(3.35*10 -4 Q 透 y i ) / (A(P 进 x i -P 透 y i )

[0108] α=R CO2 / R N2·CH4·H2

[0109] Where: R--gas i (CO2, N2, CH4) permeability (GPU);

[0110] a--Separation factor of CO2 / N2 and CO2 / CH4 of separation membrane;

[0111] Q 透 --Total molar flow rate on the permeate side (mol / s);

[0112] P 进 --Feed side pressure (MPa);

[0113] P 透 --Permeate side pressure (MPa);

[0114] A--Effective area of ​​membrane pool (m 2 );

[0115] x i --molar fraction of gas i (CO2, N2, CH4) on the feed side;

[0116] y i --Mole fraction of gas i (CO2, N2, CH4) on the permeation side.

[0117] Note: GPU = 3.35x10 -4 mol / m 2 s MPa.

[0118] The total molar flow rate of the permeate side is determined by connecting the permeate side gas to the bubble flowmeter through a hose to test its gas flow rate, and continuously recording several sets of data until the flux is stable, measuring 3 times and taking the average value. Then the total molar flow rate of the permeate side is calculated according to the following formula:

[0119] Q penetration = 1 / (2.24*10 4 )*(T / 273)*q 透

[0120] Where, T--membrane pool temperature (K);

[0121] q 透 :--Volume flow rate on the permeate side (mL / s).

[0122] Table 1 Test data statistics

[0123]

[0124] Combining Example 3 and Comparative Example 1 with Table 1, it can be seen that the composite structure formed by nano-silicon dioxide dispersed in the polyether block polyamide matrix, the addition of nano-silicon dioxide optimizes the structure and porosity of the membrane, and helps to improve the separation efficiency and separation selectivity. The molecular sieve effect of nano-silicon dioxide can help improve the selectivity of the membrane for specific gases and improve the separation efficiency.

[0125] It can be seen from Example 3 and Comparative Examples 2-3 and Table 1 that the carbon nanotube-graphene composite membrane can further improve the permeability and selectivity of the separation layer, accelerate the diffusion rate of gas molecules in the membrane, thereby improving the separation efficiency of the entire capture membrane for carbon dioxide, and compared with the use of carbon nanotubes or graphene alone, the three-dimensional structure formed by the composite has better separation efficiency and separation selectivity.

[0126] From Examples 1-3 and Table 1, it can be seen that the bisphenol A type PSF membrane also plays a role in improving the separation efficiency of the carbon dioxide capture membrane. When the carbon nanotube-graphene composite membrane is used in combination with the polyether block polyamide membrane, a synergistic effect can be formed, making the entire membrane material more selective for carbon dioxide and less permeable to other gases, thereby greatly improving the gas separation efficiency.

[0127] It can be seen from Examples 3-5 and Table 1 that the amount of nano-silicon dioxide added has an impact on the performance of the polyether block polyamide membrane, among which the amount used in Preparation Example 2 is the best in this application.

[0128] It can be seen from Example 3 and Examples 6-7 and Table 1 that the compounding ratio of carbon nanotubes and graphene will affect the final carbon dioxide separation effect of the carbon nanotube-graphene composite membrane, among which the ratio in Example 3 is the best in this application.

[0129] Combining Example 3 and Example 8-9 with Table 1, it can be seen that within the range of 4000-6000cps, polydimethylsiloxane provides an effective transmission channel for gas molecules while ensuring good adhesion. Too high viscosity will lead to a decrease in permeation rate, and too low viscosity will also adversely affect the separation factor of the carbon dioxide capture membrane.

[0130] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A carbon dioxide capture membrane, characterized in that: It comprises a base film, polydimethylsiloxane and a separation layer, wherein the separation layer comprises a polyether block polyamide film with a thickness of 20-80 μm, and the base film comprises a polyester non-woven fabric with a thickness of 0.1-0.3 mm; The preparation method of the polyether block polyamide membrane is: A1, dispersing nano-silica in ethanol, adding polyethylene glycol, using ultrasonic dispersion to obtain a nano-silica solution, dissolving polyether block polyamide in chloroform to form a uniform solution, the mass ratio of nano-silica to polyether block polyamide is (1-3):10; A2, mixing the nano-silica solution with the polyether block polyamide solution, and stirring at a speed of 1200-1500 r / min for 5-10 min; A3, the mixed solution is evenly coated on the glass substrate by a doctor blade, and dried under ventilation at 25-30°C and 40-50% humidity. After drying, a polyether block polyamide film is obtained. The polyether block polyamide film is placed in a nitrogen environment, heated to 100-140°C, kept warm for 2-4 hours, and then cooled to room temperature in a nitrogen environment; The separation layer also includes a carbon nanotube-graphene composite membrane with a thickness of 0.5-5 μm; The preparation method of the carbon nanotube-graphene composite film is as follows: B1, dispersing carbon nanotubes and graphene in N,N-dimethylformamide, the mass ratio of carbon nanotubes to graphene is (3-5):7, then adding phenylenediamine in an amount of 10-30% of the total mass of the carbon nanotubes and graphene, and uniformly dispersing by magnetic stirring to obtain a suspension; B2. Spray the suspension on the surface of the polyether block polyamide membrane, introduce nitrogen, heat to 120-140°C and keep warm for 30-60 minutes, then cool to 90-100°C and apply a pressure of 1-5 MPa for 30-60 seconds to form a carbon nanotube-graphene composite membrane.

2. The carbon dioxide capture membrane according to claim 1, characterized in that: The base film further comprises a bisphenol A type PSF film with a thickness of 100-200 μm.

3. The carbon dioxide capture membrane according to claim 1, characterized in that: The viscosity of the polydimethylsiloxane is 4000-6000 cps.

4. A method for preparing a carbon dioxide capture membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, soak the base film in water and squeeze out most of the water through a pressure roller, and then pass it through a high-speed airflow to remove water droplets on the surface; S2. A layer of polydimethylsiloxane is uniformly coated on one surface of the polyester non-woven fabric. The separation layer is bonded to the base film through the polydimethylsiloxane. The separation layer is squeezed by a roller and then put into an oven for drying. After drying, a carbon dioxide capture membrane is obtained.

5. The method for preparing a carbon dioxide capture membrane according to claim 4, characterized in that: The step S1 also includes the following operations: covering the bisphenol A type PSF film on the polyester non-woven fabric, and hot pressing at 110-125° C. and a pressure of 1-3 MPa for 5-15 minutes to obtain a base film.

Citation Information

Patent Citations

  • Polyether block polyamide / polydimethylsiloxane composite gas separation membrane, preparation method and application

    CN115608177A